The Influence Of The Profile Strengthening Of Pancasila Students (P5) Project On Student Character At SMPN 5 Payakumbuh - Akhyar, Muaddyl; Sasmi Nelwati; Khadijah, Khadijah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
The purpose of this research is to determine the relationship between SMPN 5 Payakumbuh's Pancasila Student Profile Strengthening Project (P5) and students' overall character. The correlation quantitative method was used in this study. The information is gathered through the use of questionnaires with a Likert scale. Students from eighth grade at SMPN 5 Payakumbuh made up the 66-person sample size for this study. Spearman's correlation analysis was used to study the data. Using SPSS 22, we determined that the Pancasila Student Profile Strengthening Project (P5) had no influence on students' personalities at SMPN 5 Payakumbuh. After calculating through SPSS 22, the results show that these two variables have no relationship by looking at Sig. between the two variables which is 0.960 (not correlated) because it is greater than alpha 0.05. The value of the Correlation Coefficient between the Pancasila Student Profile Strengthening Project (P5) and Student Character is +0.009. When the Correlation Coefficient is preceded by a positive sign, it means that the relationship between the two variables is a positive one. Because the correlation between X and Y is so low and has a positive shape, we can conclude that there is no relationship between them. As a result, a higher Pancasila Student Profile Strengthening Project (P5) score indicates a higher quality of character among students.